2004
DOI: 10.1172/jci200419448
|View full text |Cite
|
Sign up to set email alerts
|

Defects in nuclear structure and function promote dilated cardiomyopathy in lamin A/C–deficient mice

Abstract: Laminopathies are a group of disorders caused by mutations in the LMNA gene that encodes the nuclear lamina proteins, lamin A and lamin C; their pathophysiological basis is unknown. We report that lamin A/C-deficient (Lmna -/-) mice develop rapidly progressive dilated cardiomyopathy (DCM) characterized by left ventricular (LV) dilation and reduced systolic contraction. Isolated Lmna -/-myocytes show reduced shortening with normal baseline and peak amplitude of Ca 2+ transients. Lmna -/-LV myocyte nuclei have m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
181
0
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 337 publications
(203 citation statements)
references
References 75 publications
14
181
0
8
Order By: Relevance
“…Lamin deficiency causes abnormal nuclear architecture [20,21]: on electronmicroscopy, Lmna +/-nuclei had irregularities of shape and peripheral heterochromatin clumping [21]. We confirmed this and found that nuclei from both isolated conduction and non-conduction system myocytes of Lmna +/-mice were elongated and dysmorphic (Figure 4).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Lamin deficiency causes abnormal nuclear architecture [20,21]: on electronmicroscopy, Lmna +/-nuclei had irregularities of shape and peripheral heterochromatin clumping [21]. We confirmed this and found that nuclei from both isolated conduction and non-conduction system myocytes of Lmna +/-mice were elongated and dysmorphic (Figure 4).…”
Section: Discussionsupporting
confidence: 63%
“…Prior studies demonstrated apoptosis in ventricular myocytes from Lmna -/-mice as the probable cause for early-onset DCM and heart failure [21]. We found no apoptotic myocytes in cardiac ventricles of young adult Lmna +/-mice, despite their physical proximity to apoptotic AV nodal myocytes ( Figure 5).…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Altered lamin due to a LMNA gene mutation will develop an abnormal interaction with associated proteins resulting in disorganized cell structure and in-turn cell dysfunction [79][80][81][82] . Nikolova et al, demonstrated that in lamin A/C deficient mice the intermediate filament protein desmin, important in maintaining structural integrity of the cell, became disorganized and detached from the nuclear surface [79,83] .…”
Section: Protein-protein Interaction Hypothesismentioning
confidence: 99%
“…Lammerding et al [2004] have shown that fibroblasts from lamin A/C null mice have nuclear structural defects and attenuated NFkappaB-regulated transcription in response to mechanical or cytokine stimulation. Lamin A/C null mice develop cardiomyopathy and skeletal muscle abnormalities similar to human Emery-Dreifuss muscular dystrophy [Sullivan et al, 1999;Nikolova et al, 2004]. Hence, abnormal signal transduction may play a role the development of striated muscle disease with loss of A-type lamins.…”
Section: Concluding Speculationmentioning
confidence: 99%